Novel Endophytic Bacteria Isolates from Andaliman (Zancthoxylum acanthopodium DC.) which Potentially Inhibit Escherichia coli and Staphylococcus aureus - Rizqoh, Debie; Amelia, Aisyah; Kumala, Wulan Okta; Sipriyadi, Sipriyadi; Suryani, Utari Hartati; Sariyanti, Mardhatillah (Journal of Biomedicine and Translational Research, 2024)
Background: Irrational use of antibiotics has various side effects to resistance. Utilization of secondary metabolites of Andaliman plant endophytic bacteria (Z. acanthopodium DC) is an alternative known to act as an antibacterial to overcome this problem.Objective: This study aimed to determine the antimicrobial activity of the crude extract of Andaliman endophytic bacteria against Escherichia coli and Staphylococcus aureus.  Methods: This research is an experimental laboratory with qualitative data collection methods. The initial stages will be the isolation of endophytic bacteria from Andaliman, the antagonist test of Andaliman endophyte isolates against E. coli and S. aureus, and the extraction of endophytic bacterial isolates using ethyl acetate as solvent. An antagonistic test of bacterial isolate extract was performed using the disc diffusion method against pathogenic bacteria E. coli and S. aureus and observed by an inhibition zone. The final stage is the minimum inhibition test of endophytic isolates by dilution method on three potential endophytic isolates.Results: The results of the extraction of isolates EAA22, EAA28, EAB5, EAB6, and EAB7 Andaliman endophytic bacteria have inhibitory activity against S.aureus, and the results of the extraction of isolates EAB5, EAB6, EAA22 have inhibitory activity against E. coli.Conclusion: Endophyte bacteria isolates from Andaliman produce antibacterial compounds against E. coli and S. aureus.